Efektivitas Metode Bermain Angka Terhadap Kecemasan Belajar Matematika pada Siswa Kelas V Sekolah Dasar - Sri Rahayu; Eva Meizara Puspita Dewi; Andi Halima (Edu Berkah Khatulistiwa, 2023)
Mathematics lessons are part of a definite science and have a structure of interconnected patterns. However, some students avoid and easily get bored when math lessons begin. The fun learning model has a play concept based on this. This study aims to test the effectiveness of the numbers game method on the math anxiety of fifth grade elementary school students. This study used a pretest-posttest control group design experimental design. The subjects in this study were 20 people who were divided into the experimental group and the control group. Respondents in this study were V grade students at the SD Inpres Bertingkat Mamajang II, Makassar City. The measuring tool used in this research is the mathematics learning anxiety scale. The data analysis technique uses hypothesis testing, namely the Independent T-Test and Paired Sample T-Test. The results of the hypothesis test show that the significance value is ρ = 0.014 < 0.05, so the hypothesis in this study is accepted so that it is said that giving the number playing method can be used as a method to reduce anxiety learning mathematics. The implication of this research is that the number playing method can be used as a method to reduce math anxiety in students.